European women: Why do(n't) they work? - Véronique Genre; Ramón Gómez-Salvador; Ana Lamo (European Central Bank (ECB), 2005)
This paper provides an empirical study of the determinants of female participation decisions in the European Union. The analysis is performed by estimating participation equations for different age groups (i.e. young, prime-age and older females), using annual data for a panel of 12 EU-15 countries over the period 1980-2000. Our findings show that the strictness of labour market institutions negatively affects the participation rate. Decisions linked to individual preferences with regards to education or fertility are also found relevant to participation of the youngest and prime-age females respectively. The inclusion of a proxy to capture cohort effects is crucial in order to explain the oldest females' participation.
Keywords: J21; 330; labour force participation; Labour market institutions; Weibliche Arbeitskräfte; Schätzung; EU-Staaten